Synthesis, Characterization and Biological Studies of Novel Imines and Azetidinones Derivatives of Haloaryloxy Moiety - Kumar Fuloria, Neeraj; Singh, Vijender; Shaharyar, Mohd.; Ali, Mohd. (Asian Journal of Chemistry, 2010)
Haloaryloxy moiety on refluxing with chloroethyl acetate in the presence of potassium carbonate and acetone yielded ethyl halolaryloxy acetate (1), which was reacted with hydrazine hydrate to produce haloaryloxyacetyl hydrazine (2), which on treatment with aromatic aldehydes yields imines (3A-J) and subsequently into azetidinones (4A-J). The novel series of compounds were elucidated on the basis of spectral studies and screened for antibacterial and antifungal studies.